Improving Student Teacher Preparedness in Reading Instruction - Jennifer Milne; Keith J. Topping (Education Sciences)
Background: Learning to read is a complex linguistic and cognitive process. Despite the ever-growing body of empirical evidence, the complex knowledge and skills needed to teach all children to read have not been passed to trainee and in-service teachers. Methods: This study examined the delivery and evaluation of a short, intense literacy elective course, with 9 h of learning for trainee primary/elementary teachers, focused on the key knowledge areas of phonemic awareness, phonics instruction, fluency, vocabulary, text comprehension, and reading assessment. An open questionnaire was administered to 16 trainee teachers: they completed this same questionnaire prior to beginning the elective and again after. The questionnaire focused on the understanding of quality reading instruction, at-risk readers, and provision for struggling readers. The data were analyzed using a qualitative interpretational analysis (QIA). Results: The lowest levels of understanding at the outset were in reading fluency instruction and reading assessment: these areas then showed the greatest knowledge development. Importantly, by post test, participants increased access to evidence-based literature and resources. Feedback demonstrated the high value placed by the group on this learning. Conclusions: This approach improved trainee teachers’ content knowledge to teach reading in a short time. Initial Teacher Education should increase its focus on reading, a crucial foundation skill.